Respiratory Microbiome Profile of Pediatric Pulmonary Hypertension Patients Associated With Congenital Heart Disease. Issue 1 (10th November 2022) - Wang, Ting; Xing, Yue; Peng, Bingming; Yang, Kai; Zhang, Chenting; Chen, Yuqin; Geng, Gang; Li, Qubei; Fu, Jian; Li, Mi; Luo, Zhengxiu; Fu, Zhou; et al.
Abstract : Background: Pulmonary hypertension (PH) associated with congenital heart disease (CHD) is the most common type of PH in pediatric patients. The airway microbiome profile in CHD-PH patients remains rarely studied. Methods: A total of 158 children were recruited for collection of oropharyngeal swabs to sequence the 16S ribosomal RNA ( 16S rRNA) V3-V4 region of respiratory microbiome, to establish a correlation between these bacterial groups and echocardiography indicators in CHD-PH patients. Results: Bacterial α- and β-diversity of the airway microbiome indicated a significantly lower richness in the CHD-PH group and compositional differences associated with the specific taxa and their relative abundances in the upper respiratory tract. Principal coordinate analysis showed that the pharynx microbiota composition in the CHD-PH group varied from that in the CHD or control group. The linear discriminant analysis effect size also highlighted an increased presence of Streptococcus and Rothia in pediatric CHD-PH patients. Comparison of microbial composition between pediatric and adult PH patients showed significant differences and separation of microbiota. The correlation between bacterial abundance and transthoracic echocardiography indexes in CHD-associated PH indicated that different groups of microbiomes may be related to different PH grades. Conclusions: In summary, our study reported the systematic definition and divergent profile of the upper respiratory tract microbiota in pediatric PH patients, CHD and reference subjects, as well as between pediatric and adult PH patients.